(untitled) (Research, Society and Development, 2021)
The human identification, one of the most searched areas on the forensic field, is based on the application of methods and techniques to individualize people. The cheiloscopy is a method of human identification based in the study of morphological characteristics of labial grooves, considered unique patterns for every person, same as finger prints. We evaluated the existing scientific evidence about cheiloscopy as a method of human identification through a systematic review, based on the Preferred Report of Systematic Reviews and Meta-Analysis (PRISMA) protocol. The searches were performed in the databases: Web of Science, Pubmed, Scopus, Cochrane, Lilacs and Sigle following the strategy of the acronym PICO/PECO. 10,715 records were recovered and, after removing duplicates and initial screening, 26 articles were read in full. Ultimately, 22 articles remained, of which 21 had a cross-sectional and 1 longitudinal design. The assessment of methodological quality, performed by the QUADAS-2, indicated that all studies met more than 80% of the quality requirements. The classification systems used for analysis varied between the studies, with Suzuki and Tsuchihashi being the most used (82%). To search the more common standards of labial grooves and their unicity, the studies used statistical analysis that involved 7 types of tests and in 5 studies were used descriptive statistics. We concluded that cheiloscopy is an effective method for human identification, being faster and low budget. However, the method is not effective to estimate the sex and evidences are still needed to confirm it’s applicability on the analysis of the parental relation.